Transforming Sustainable Tourism and Hospitality through Innovative Smart Practices - Kumari, Madhu; Kumar, Suneel; Devi, Nisha; Kumar, Anil (Palash: A Journal of Hospitality and Tourism Service Management, 2025)
Digitization encompasses the transformation of analogue  information into a digital format, spanning a broad spectrum  of data conversion. The aim of endeavours like Digital India  is to harness the power of technology to elevate productivity  through the effective use of digitized data and information.  By integrating digital tools into business processes, these  initiatives seek to optimize efficiency and foster growth within  the economy. Since 2014, the government has placed a strong  emphasis on digitization. Among the industry’s leading the  charge in this regard is the tourism and hospitality sector,  which is still seeing rapid growth. This dynamic arena reflects  the dynamics of several players in the tourism industry. The  tourist sector has embraced digitalization and incorporated  it into its operations to provide new travel routes and ways  to increase guest satisfaction. It’s a prevalent misconception  that digitalization in tourism is restricted to online hotel  reservations and electronic payments. UN Secretary General Antonio Guterres emphasizes the pivotal role of  tourism in preserving both natural and cultural heritage.  However, the expansion of tourism in various regions and  countries brings significant impacts on natural resources,  consumption patterns, pollution levels, and social dynamics.  “Sustainable tourism and hospitality management” aims to  achieve a balanced integration of three key  facets of tourism development: environmental,  economic, and socio-cultural. Consequently, this  concept has gained significant traction among  travel agencies, emphasizing the importance  of fostering harmony among these aspects for  long-term viability and positive impact. The  objective of this delicate equilibrium is to ensure  the enduring sustainability of the tourism sector.  In order to be sustainable, we need to consider  the social and economic effects of our actions  on people as well as the environment. Therefore,  the foundational principles of sustainable  tourism encompass social equity, environmental  preservation, and economic prosperity
Keywords: Hospitality; Sustainable Tourism; Smart Practices; Innovation